Detection of LongR3‐IGF‐I, Des(1‐3)‐IGF‐I, and R3‐IGF‐I using immunopurification and high resolution mass spectrometry for antidoping purposes. Issue 7 (22nd February 2021) - Mongongu, Cynthia; Coudoré, François; Domergue, Valérie; Ericsson, Magnus; Buisson, Corinne; Marchand, Alexandre
Abstract: Insulin‐like growth factor‐I (IGF‐I) and its analogs LongR 3 ‐IGF‐I, Des(1‐3)‐IGF‐I, and R 3 ‐IGF‐I are prohibited substances in sport. Although they were never approved for use in humans, they are readily available as black market products for bodybuilding and can be used to enhance physical performance. This study's aims were to validate a fast and sensitive detection method for IGF‐I analogs and to evaluate their detectability after intramuscular administration in rats. The sample preparation consisted of an immunopurification on MSIA™ microcolumns using a polyclonal anti‐human‐IGF‐I antibody. The target substances were then directly analyzed by nano‐liquid chromatography coupled with high‐resolution mass spectrometry. Abundant signs of lower quality, oxidized peptide forms were found in black market products, justifying the need to monitor at least both the native and mono‐oxidized forms. The analytical performance of this method (linearity, carry over, detection limits, precision, specificity, recovery, and matrix effect) was studied by spiking the analogs into human serum. Following a single intramuscular administration (100 μg/kg) in rats, detection was evaluated up to 36 h after injection. While unchanged Des(1‐3)‐IGF‐I and R 3 ‐IGF‐I were detected until 24 h after administration, LongR 3 ‐IGF‐I disappeared rapidly after 4 h. Des(1)‐LongR 3 ‐IGF‐I, a new N‐terminal Long‐R 3 ‐IGF‐I degradation product, was detected in addition to Des(1‐10)‐LongR 3 ‐IGF‐I and Des(1‐11)‐LongR 3− IGF‐I: the latter was detected up to 16 h. The same products were found after in vitro incubation of the analogs in human whole blood, suggesting that observations in rats may be extrapolated to humans and that the validated method may be applicable to antidoping testing. Abstract : An analytical method for the detection of LongR 3 ‐IGF‐I, Des(1‐3)‐IGF‐I, and R 3 ‐IGF‐I in blood was validated using immunopurification‐based sample preparation combined with nano‐LC/HRMS detection. This strategy allowed detection at low concentrations with high specificity. In vivo (single intra‐muscular administration in rats) and in vitro (rat and human whole blood) experiments on these target substances demonstrated that LongR 3 ‐IGF‐I, Des(1‐3)‐IGF‐I, and R 3 ‐IGF‐I misuse could be successfully detected in antidoping tests.